2017
DOI: 10.1002/pro.3316
|View full text |Cite|
|
Sign up to set email alerts
|

Large cosolutes, small cosolutes, and dihydrofolate reductase activity

Abstract: Protein enzymes are the main catalysts in the crowded and complex cellular interior, but their activity is almost always studied in dilute buffered solutions. Studies that attempt to recreate the cellular interior in vitro often utilize synthetic polymers as crowding agents. Here, we report the effects of the synthetic polymer cosolutes Ficoll, dextran, and polyvinylpyrrolidone, and their respective monomers, sucrose, glucose, and 1-ethyl-2-pyrrolidone, on the activity of the 18-kDa monomeric enzyme, Escherich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 78 publications
4
37
1
Order By: Relevance
“…These limitations do not, however, change the fact that the hard-core component has a larger effect on the domain-swapped dimer. We did not apply the theory to the synthetic polymers, because these macromolecules cannot be accurately modeled as spheres, because, at the high concentrations used here (39)(40)(41), the individual polymer molecules overlap to form a mesh (42). The reason is exemplified by the concentration dependence of viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…These limitations do not, however, change the fact that the hard-core component has a larger effect on the domain-swapped dimer. We did not apply the theory to the synthetic polymers, because these macromolecules cannot be accurately modeled as spheres, because, at the high concentrations used here (39)(40)(41), the individual polymer molecules overlap to form a mesh (42). The reason is exemplified by the concentration dependence of viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…Inert macromolecules such as dextran, Ficoll, polyethylene glycol (PEG) or proteins (e. g. albumin) are commonly used to mimic cellular crowding in vitro . These experiments have demonstrated that crowding stabilizes proteins, modulates enzymatic activity,, and enhances association …”
Section: Figurementioning
confidence: 99%
“…3 To mimic cellular crowding in vitro, inert macromolecules such as dextran, Ficoll, polyethylene glycol (PEG) or proteins (e.g., albumin) can be added to the buffer. 4 In vitro studies with inert macromolecules added to the buffer demonstrate that crowding compacts and stabilizes proteins, 5,6 modulates enzymatic activity, 7,8 and enhances association. 9 Yet crowding alone cannot account for all interactions inside cells; Superoxide dismutase, 10 variable major protein-like sequence expressed (VlsE), 11,12 B1 domain of protein G (GB1), 13 and chymotrypsin inhibitor 2 (Cl2) 14 all are destabilized inside cells compared to in vitro.…”
Section: Introductionmentioning
confidence: 99%